An aggressive hematolymphoid neoplasm with homozygous SMARCB1 loss shows response to EZH2 inhibition - Iman Sarami; Amy S. Duffield; Suchitra Sundaram; Douglas I. Lin; Christian Salib; Shafinaz Hussein; Siraj El Jamal; Nasrin Ghesani; Busra Cangut; Bruce E. Petersen (Haematologica)
Not available.